find lim x->0 3- sqrt x+9/-x

1 answer

In general, when there is a sum or difference of square-root terms, multiplying both numerator and denominator by the conjugate is a good strategy.

Lim (3- sqrt( x+9))/(-x )
x->0
= Lim (3-sqrt(x+9))(3+sqrt(x+9))/[(-x)(3+sqrt(x+9)]
x->0
= Lim (9-(x+9))/[(-x)(3+sqrt(x+9)]
x->0
= Lim (-x)/[(-x)(3+sqrt(x+9)]
x->0
= Lim 1/(3+sqrt(x+9)
x->0
=1/6
Similar Questions
  1. Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work.sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2)
    1. answers icon 1 answer
    1. answers icon 2 answers
  2. 1. Evaluate tan[sin^-1(a)].a. [sqrt(1-a^2)]/1-a^2 b. [sqrt(1-a^2)]/a c. sqrt(1-a^2) d. {a[sqrt(1-a^2)]}/1-a^2 I do not know the
    1. answers icon 3 answers
    1. answers icon 6 answers
more similar questions